Activités artisanales sur la rive droite de la Vesle à Reims/Durocortorum - Émilie Jouhet; Michaël Brunet; Pierre Mathelart; Véronique Matterne (Gallia)
Located in the southwestern part of the ancient city, the re-investment and development of the former ZAC du Vieux-Port, along the boulevard Dr. Henri-Henrot in Reims, was preceded by a major rescue archaeology excavation in 2008-2009, extending over a surface of 4,000 m2 and descending more than 3 m of stratigraphy. This archaeological operation is the first to have provided the opportunity to uncover and study the right bank of the Vesle River during Antiquity, spanning a length of nearly 50 m. Moreover, this location is situated in an area where the water table is shallow and allowed for excellent preservation of plant remains, as well as artifacts and architectural elements composed of perishable materials. Initially located in a flood zone, the excavated area was developed to accommodate a dense occupation centered on various artisanal activities during the first three centuries AD. If, during the first three quarters of the 1st c. AD, only a dike and a wooden structure intended to stabilize the banks protected the initial circulation routes, during the 2nd and 3rd c. AD, several massive quays made of chalk and oak planks followed. They allowed for the installation of new pathways associated with a secondary decumanus. Above all, they also allowed for initially limited masonry construction, which subsequently became increasingly important, taking the form of relatively consistently shaped cells or small rooms. Initially and primarily in the northern half of the site, these rooms would accommodate metallurgical activity. First of all, this was deduced from the discovery of a hundred or so vase fragments intended for use in metal alloy creation, and which can be grouped together under the term “crucible.” Possible forge workshops were also discovered, initially within a small building, then within a vast construction, counting at least fourteen other rooms. Even if the function of each room has not been identified, a certain number of recurring equipment items may be linked to metallurgical activity: numerous post holes, several pits that yielded large quantities of charcoal, limestone with a polished and reddened appearance, suggesting their use as anvils, and up to three hearths per space, totaling more than a dozen. Moreover, the use of all these structures is also marked by the presence of an accumulation of blackish-gray silty-clay levels, covering about 70% of the total surface of the building, which contained a large quantity of battitura. Finally, a few characteristic clay or iron objects (such as tongs) also reinforce the hypothesis of a forge located on site or, are at least bolster the presence of a relationship to utilitarian and artisanal activities. In the absence of roughing, finished products, or manufacturing failures on site, it remains impossible to identify the precise type of production intended for the metal work. Moreover, specific remains and a high density of certain objects, concentrated in the southern half of the excavation, argue in favor of the presence of textile activity on the site or within its surroundings. A comb and 74 fragments of iron comb teeth found in the river backfill attest to the preparation of raw material in the area. Retrieved objects related to subsequent stages of spinning activity are rarer, and include two small fragments of boxwood spindles, as well as two spindle whorls made of boxwood and chalk. Several wooden spools appear to be associated with an intermediate stage of textile work between spinning and weaving. Weaving activities are illustrated by material retrieved within seven cells, likely used for handicrafts or for storing raw materials. A large number of weights were been found therein, as well many sewing needles. Structures related to fabric manufacturing have also been identified and take the form of pits whose primary filling is composed of relatively compact and homogeneous yellow to orange colored clay. The geological analysis results performed on the stored clay demonstrated that they were 100% composed of smectite (whose geographical and geological origin could not be determined). Unsuitable for the manufacture of pottery or terracotta elements, smectite clay is a “fuller’s earth” which, as its name indicates, can be used for treading and dyeing, within the vats or tubs wherein the textile fibers of the wool are softened and colored. The river levels also yielded an exceptional series of twenty-nine brushes, mostly fragments of wool brushes, all rather similar in type. The brushes were likely used to remove the down from the sheets of fabric produced, which would have been stretched on a pole, and the fluff subsequently removed by cutting, thereby refining the fabric. Finally, in the absence of vats or tubs, the practice of dyeing in this sector of the city has also been deduced from the high rates of certain plant remains within the carpological samples. This may also be echoed by the significant representation of Lipari amphorae within the assemblage. The latter were likely used to market alum, used in the dye fixation process. Over the course of the 4th c. AD, a large building was erected within the excavated area. Given the massive nature of this construction, it seems likely that access to it from the city and the river was maintained. However, the demolishing of the most recent layers explains in part why no road or quay level related to this phase was discovered. In addition, the junction between this building and the river lays outside the area of study. The builders worked from the years 306-307, using a technique specific to a wet environment, which they mastered perfectly. Measuring nearly a meter in diameter, the walls of this building rest on hundreds of oak piles driven into the underlying clay sediments, belonging to an ancient branch of the river. In addition, this building housed a series of juxtaposed ovens, separated by low masonry walls. The function of this complex, which was destroyed at the turn of the 4th and 5th c. AD, remains a mystery.